Association between Serum Ferritin and Blood Lipids: Influence of Diabetes and hs-CRP Levels - Lianlong Yu; Jingyi Yan; Qian Zhang; Hong Lin; Lichao Zhu; Qiangqiang Liu; Changsheng Zhao (Journal of Diabetes Research)
This study is aimed at exploring the relationship between serum ferritin and blood lipids and the influence of diabetes and different hs-CRP levels. A total of 8163 subjects were analyzed. Participators were classified according to serum ferritin, diabetes, and two hs-CRP levels. Blood lipids were determined using standardized methods and conditions. Except for HDL-C, there was a significant increase in blood lipids in the progressive ferritin group with normal hs-CRP levels (P<0.05). But HDL-C was just the opposite (P<0.0001). In nondiabetic patients, TG, TC, and LDL-C were significantly elevated in the progressive ferritin group (P<0.05). And, HDL-C was just the opposite (P<0.05). The generalized linear model and the parsimonious model showed that serum TG was positively correlated with ferritin, and LDL-C was negatively correlated with ferritin (P<0.05). But the correlation between LDL-C and ferritin was broken (P>0.05). After a sufficient adjustment, there was a positive correlation between serum TG and ferritin and a negative correlation between LDL-C and ferritin. Nonetheless, a negative correlation between LDL-C and ferritin is influenced by diabetes frailly. And, there was no change of relationship between lipids and ferritin in different hs-CRP levels. We found a real relationship between ferritin and lipids after sufficient adjustment for confounders.